2004
DOI: 10.1176/appi.ps.55.6.706
|View full text |Cite
|
Sign up to set email alerts
|

Use of Psychotropic Medications by Youths in Therapeutic Foster Care and Group Homes

Abstract: This article examines the use of psychotropic medications among youths in residential community-based placements. Data are from a study funded by the National Institute of Mental Health of therapeutic foster care (June 1999 through May 2001) and group homes (January through June 2001). Data were collected from staff by means of in-person interviews. Many youths in both settings received psychotropic medications, and approximately one-half were taking multiple psychotropic medications. After the authors control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 8 publications
4
50
1
3
Order By: Relevance
“…Psychotropic prevalence for youth in foster care ranges from 14% to 30% in community settings [1][2][3][4] and as high as 67% in therapeutic foster care and 77% in group homes. 5 Many youth in foster care receive more than 1 psychotropic medication, with as many as 22% using Ն2 medications from the same class. 6 Among youths with autism who were in foster care, 21% received Ն3 medications from different classes concomitantly for at least 30 days, compared with 10% among youths with autism and eligible for Medicaid through a disability status.…”
mentioning
confidence: 99%
“…Psychotropic prevalence for youth in foster care ranges from 14% to 30% in community settings [1][2][3][4] and as high as 67% in therapeutic foster care and 77% in group homes. 5 Many youth in foster care receive more than 1 psychotropic medication, with as many as 22% using Ն2 medications from the same class. 6 Among youths with autism who were in foster care, 21% received Ն3 medications from different classes concomitantly for at least 30 days, compared with 10% among youths with autism and eligible for Medicaid through a disability status.…”
mentioning
confidence: 99%
“…Although TFC is often considered as a substitute for group care, the population of youths served in TFC and group care show some differences on average. Studies that have descriptively compared TFC and group care have found that TFC youths are less disturbed (Berrick, Courtney & Barth, 1993), less likely to be taking psychotropic medications (Breland-Noble et al, 2004), and more likely to receive community-based supplementary services (Breland-Noble, Farmer, Dubs, Potter & Burns, 2005) than group care youth.However, it is not clear whether aggregate differences in youth populations served by TFC and group care are intentional or accidental. While policy and practice trends suggest that less troubled youth should be placed in less-restrictive settings, not enough evidence is available to anticipate which youth are best served in which environments.…”
mentioning
confidence: 99%
“…Post out-of-home variables are measured in the 6 months after the out-of-home treatment episode. Prior to out-of-home episode variables are measured in the 6 months prior to the out-of-home treatment episode homes and treatment foster care (Breland-Noble et al 2004;Najjar et al 2004;Zito et al 2008), and more specifically antipsychotic medications (Zito et al 2008). Fifteen percent of youth returned to out-of-home treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among those with high rates of utilization were children and youth who have been removed from the home for mental health treatment (Breland-Noble et al 2004;Zito et al 2008). High rates of psychotropic medication use have been found among children in residential group homes and treatment foster care (Breland-Noble et al 2004;Najjar et al 2004). Fiftythree percent of youth in foster care who received psychotropic medications were receiving antipsychotic medications (Zito et al 2008).…”
Section: Introductionmentioning
confidence: 99%